Origin of low thermal hysteresis in shape memory alloy ultrathin films. (15th January 2016) - Zong, Hongxiang; Ni, Ze; Ding, Xiangdong; Lookman, Turab; Sun, Jun
Abstract: Hysteresis in martensitic transformations (MT) limits the usefulness of shape memory alloys (SMAs) in nanosized devices that require high sensitivity, high durability and high energy efficiency. Previous studies have shown that the MT is hindered in the surface region of nanosized SMAs, and therefore there is little hysteresis. However, we find that the hysteretic behavior in SMA nanofilms is not related to the MT suppression. Rather, the decrease in hysteresis is due to weaker spontaneous lattice distortion and spatial heterogeneity, leading to a more continuous phase transformation process. We demonstrate this by designing two classes of nano-sized SMAs, a free-standing Ni62.5 Al37.5 film in which the surface region promotes MT, and a multilayer of Fe–Ni62.5 Al37.5 –Fe in which the interface region suppresses MT. Both cases show a decrease in hysteresis with decreasing film thickness. Our findings suggest a method to reduce hysteresis in conventional bulk SMAs. Graphical abstract: